The South African new educational environment: - Genevieve Louw; Sonja Verwey (Communicare)
South African educational institutions are confronted by a myriad of new policies, legislation and qualification frameworks, resulting in extensive transformation of the South African educational landscape. This article explores the effect that the pursuit of transformation objectives is having on communication training and education at universities and technikons. A number of transformation priorities for communication education and training is also identified.